Digitalization: Labour markets - Alex Chernoff; Gabriela Galassi (Bank of Canada, 2023)
In this paper, the authors assess the relationship between digitalization and labour demand and supply, and how this relationship affects wages and income inequality. We also explore implications of recent digitalization trends for the future of work.
Keywords: I; I2; I23; J; J2; J23; J24; O; O3; O33; 330; Digitalization; Labour markets